Multibeam bathymetry raw data (Kongsberg EM712 entire dataset) of RV MARIA S. MERIAN during cruise MSM99/2 - Böttner, Christoph; Schmidt, Christopher (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM99/2 using a Kongsberg EM 712 multibeam echosounder. The expedition took place during 26.03.2021 - 04.04.2021 from Emden to Emden (Germany) in the North Sea. Data were recorded in the EEZ of Germany. The aim of MSM99/2 was to investigate the periodic emergence of pockmarks north of Helgoland in the German Bight, North Sea. Sound velocity profiles (SVP) were applied on the data for calibration. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Please see the cruise report for details.
Keywords: EM712; German Bight; Helgoland; Multibeam Data; North Sea; pockmarks